Postprandial changes in gene expression of cholesterol influx and efflux mediators after intake of SFA compared with n-6 PUFA in subjects with and without familial hypercholesterolaemia: secondary outcomes of a randomised controlled trial. (2019) - Øyri, Linn K. L.; Narverud, Ingunn; Bogsrud, Martin P.; Hansson, Patrik; Leder, Lena; Byfuglien, Marte G.; Veierød, Marit B.; Thoresen, Magne; Ulven, Stine M.; Holven, Kirsten B.
Abstract: Abstract: The long-term cholesterol-lowering effect of replacing intake of SFA with PUFA is well established, but has not been fully explained mechanistically. We examined the postprandial response of meals with different fat quality on expression of lipid genes in peripheral blood mononuclear cells (PBMC) in subjects with and without familial hypercholesterolaemia (FH). Thirteen subjects with FH (who had discontinued lipid-lowering treatment ≥4 weeks prior to both test days) and fourteen normolipidaemic controls were included in a randomised controlled double-blind crossover study with two meals, each with 60 g of fat either mainly SFA (about 40% energy) or n -6 PUFA (about 40% energy). PBMC were isolated in fasting, and 4 and 6 h postprandial blood samples. Expression of thirty-three lipid genes was analysed by reverse transcription quantitative PCR. A linear mixed model was used to assess postprandial effects between meals and groups. There was a significant interaction between meal and group for MSR1 ( P = 0·03), where intake of SFA compared with n -6 PUFA induced a larger reduction in gene expression in controls only ( P = 0·01). Intake of SFA compared with n -6 PUFA induced larger reductions in gene expression levels of LDLR and FADS1/2, smaller increases of INSIG1 and FASN, and larger increases of ABCA1 and ABCG1 ( P = 0·01 for all, no group interaction). Intake of SFA compared with n -6 PUFA induced changes in gene expression of cholesterol influx and efflux mediators in PBMC including lower LDLR and higher ABCA1/G1, potentially explaining the long-term cholesterol-raising effect of a high SFA intake.